A fresh approach to Indigenous Business Education. Issue 7 (19th August 2014) - Bajada, Christopher; Trayler, Rowan
Abstract : Purpose: The social and economic disadvantaged confronted by many Indigenous Australians is well known. A close look at Indigenous employment highlights that Indigenous Australians are substantially under‐represented in the technical and professional areas of business and management. Closing the gap and improving the social and economic outcomes requires a greater focus in these areas. This paper outlines the design of an innovative undergraduate business degree for Indigenous students that: (i) meets the targets set by government; (ii) produces the "T‐shaped" graduate expected by business (disciplinary and interdisciplinary knowledge and soft skills); (iii) addresses the employment needs of the Indigenous community; and (iv) provides the building blocks for Indigenous students to enrol in postgraduate business courses. Design/methodology/approach: The development of the Bachelor of Business Administration (Indigenous) provided an opportunity to address the needs of Indigenous Australians in a curriculum that is not only interdisciplinary but also taught by indigenous and non‐Indigenous academics. The paper outlines how the review was shaped, the innovative mode of delivery and the interdisciplinary nature of the curriculum. Findings: The course contextualises the study of business within an Indigenous perspective to demonstrate how Indigenous studies not only contributes to empowering the individual but also how business education plays a critical role in repositioning Indigenous people in their local communities and society more broadly. Originality/value: This paper demonstrates an integrated approach to business education focusing on the professional, technical and managerial roles in business that are in short supply in Indigenous communities.